Pengaruh Kepadatan Kandang Terhadap Berat dan Persentase Bagian Karkas Ayam Broiler Umur 5 Minggu - I Putu Subagia; Ni Ketut Mardewi; I Gusti Ayu Dewi Seri Rejeki (GEMA AGRO, 2019)
Poultry commodities that have the greatest potential to be developed are broiler chickens, because the growth is so fast that the maintenance period is relatively short. One important environmental factor to pay attention is maintenance management, especially housing. High cage density causes chicken body weight gain to be smaller compared to low cage density, so research needs to be done to find out how much the ideal density of cage. The research design used was a completely randomized design (CRD) with 3 treatments and 3 replications. P1 is 8 chickens/m2, P2 (10 chickens/m2), and P3 (12 chickens/m2). There are 9 cages and 90 broilers used. The level of cage density gave no significant effect (P>0.05) on the weight and percentage of carcass parts of broilers aged 5 weeks. of all the variables, there was a tendency for an increase in yield in the treatment of cage density of 10 m2/broiler chickens maintained for 5 weeks (P>0.05). From the results of this study it can be concluded that the density of the cage has no effect on the weight and percentage of carcass parts of broiler chickens aged 5 weeks. It can also be recommended to farmers to use cage density of 12 chickens/m2 in the maintenance of broiler chickens aged 5 weeks because they are still able to produce weight and percentage of good carcass parts